Globalization and the African Economic Crisis: An Overview - Onimisi, Timothy (International Journal of Social Sciences and Management, 2014)
Globalization is a phenomenon that is fast sweeping through the world and of which Africa is not immune to, and it is very instrumental in molding the world from politics to economy, from religion to culture. In understanding the relationship that existing between the African economy and the wider world some economic indicators will be a useful tool in this analysis. The research focuses on how globalization has shaped the African economy, taking into cognizance the impact of the concept on African’s key sectors like Poverty, Trade Relations, and Debt Burden. Haven identified the crisis associated with globalization as it relate to Africa’s economy, the research recommend sustained and profitable engagement of Africa with the developed world and good governance is needed to strengthen the development process in African states if these recommendations are implemented the African economy will be strategically positioned in the complex theater of world economy. DOI: http://dx.doi.org/10.3126/ijssm.v1i3.10477 Int. J. Soc. Sci. Manage. Vol.1(3) 2014: 113-119